The third freedom : ending hunger in our time - McGovern, George S. (George Stanley), 1922-2012 (2002)
"In The Third Freedom, McGovern lays out a workable and affordable five-point program to end world hunger. The basic facets include these steps: the United States should take the lead within the UN in working toward a universal school lunch program; the American supplemental nutrition program for low-income women, infants, and children should go worldwide; the United Nations must establish food reserves around the globe; developing countries must be assisted in improving their own farm production, food processing, and food distribution; high-yielding, scientific agriculture, including genetically modified crops, must be further encouraged and developed.".